Multiple species within the Striated Prinia Prinia crinigera–Brown Prinia P. polychroa complex revealed through an integrative taxonomic approach. (28th August 2019) - Alström, Per; Rasmussen, Pamela C.; Sangster, George; Dalvi, Shashank; Round, Philip D.; Zhang, Ruiying; Yao, Cheng‐Te; Irestedt, Martin; Le Manh, Hung; Lei, Fumin; Olsson, Urban
Abstract : We re‐evaluated the taxonomy of the Striated Prinia Prinia crinigera –Brown Prinia P. polychroa complex using molecular, morphological and vocal analyses. The extensive seasonal, sexual, age‐related, geographical and taxon‐specific variation in this complex has never before been adequately studied. As no previous genetic or vocal analyses have focused on this group, misinterpretation of taxonomic signals from limited conventional morphological study alone was likely. Using mitochondrial and nuclear DNA, we found that P. crinigera sensu lato ( s.l .) comprises two non‐sister groups of taxa (Himalayan crinigera and Chinese striata groups) that differ substantially morphologically and vocally and that are broadly sympatric in Yunnan Province, China. Prinia polychroa cooki (Myanmar) and P. p. rocki (southern Vietnam) are each morphologically, vocally and genetically distinct. Thai, Cambodian and Laotian populations formerly ascribed to P. p. cooki are morphologically and vocally most similar to and most closely related to Javan P. p. polychroa, and require a new name, proposed here. Prinia p. bangsi of Yunnan is part of the crinigera group rather than of P. polychroa, and hence there is no evidence for sympatry between P. polychroa s.l . and P. crinigera s.l ., nor of the occurrence of P. polychroa in mainland China or Taiwan. We recommend the recognition of five species in the complex, with the following suggestions for new English names: Himalayan Prinia P. crinigera sensu stricto ( s.s .; with subspecies striatula, crinigera, yunnanensis and bangsi ); Chinese Prinia P. striata (subspecies catharia, parumstriata and striata ); Burmese Prinia P. cooki (monotypic); Annam Prinia P. rocki (monotypic) and Deignan's Prinia P. polychroa s.s . (subspecies Javan polychroa and the new Southeast Asian taxon). This study underlines the importance of using multiple datasets for the elucidation of diversity of cryptic bird species and their evolutionary history and biogeography.